Amino-based covalent organic frameworks for a wide range of functional modification. (15th June 2022) - Zhao, Yuling; Xu, Xianhui; Xu, Chang; Meng, Deyuan; Liang, Xiaoqian; Qiu, Jikuan
Abstract : A versatile protocol for modification of amino-based COFs with desired functionalities was developed via transforming the unreachable amino groups into imine, thiourea, amide and azo-based functional groups. Abstract : As a new type of porous crystalline material, covalent organic frameworks (COFs) have shown great potential in many application fields. Postsynthetic modification (PSM) is a prevalent and useful strategy for producing new COFs with desired functionalities. Herein, we report a general method for COF post-functionalization that involves the introduction of amino functional groups (–NH2 ) into the framework as anchoring sites. By this strategy, a variety of COFs with desired functionalities were prepared under ambient conditions by transforming –NH2 into imine, thiourea, amide and azo-based functional groups. We believe this work will provide an opportunity to create porous materials with augmented properties and performances and expand their practical application.